2022
DOI: 10.3390/jcm11051444
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lenvatinib and Sorafenib in the Real-World First-Line Treatment of Advanced-Stage Hepatocellular Carcinoma in a Taiwanese Population

Abstract: Aim: Currently, atezolizumab combined with bevacizumab is the standard first-line treatment for unresectable hepatocellular carcinoma (HCC), but lenvatinib or sorafenib are still recommended for these patients for some reasons. The aim of the study was to determine the outcomes of Taiwanese patients with advanced-stage HCC who received lenvatinib or sorafenib. Methods: Data on patients with BCLC stage C HCC who were receiving lenvatinib or sorafenib as the first-line therapy from May 2018 to August 2020 was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 17 publications
2
28
0
1
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the fourth leading cause of cancer related mortality [ 1 ], with more than 80% of patients diagnosed at an advanced unresectable stage and curative options such as surgical resection and liver transplantation are excluded at these advanced stages, and therefore only limited effective treatment options remain [ 2 ]. Sorafenib and recently lenvatinib, have been approved as first line systemic treatment options for advanced HCC patients, as evidenced by several studies demonstrating the survival benefit of sorafenib and lenvantinib treatment [ 3 ]. The SHARP trial has demonstrated the survival benefit of sorafenib compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocellular carcinoma (HCC) is one of the most common cancers worldwide and the fourth leading cause of cancer related mortality [ 1 ], with more than 80% of patients diagnosed at an advanced unresectable stage and curative options such as surgical resection and liver transplantation are excluded at these advanced stages, and therefore only limited effective treatment options remain [ 2 ]. Sorafenib and recently lenvatinib, have been approved as first line systemic treatment options for advanced HCC patients, as evidenced by several studies demonstrating the survival benefit of sorafenib and lenvantinib treatment [ 3 ]. The SHARP trial has demonstrated the survival benefit of sorafenib compared to placebo.…”
Section: Introductionmentioning
confidence: 99%
“…The SHARP trial has demonstrated the survival benefit of sorafenib compared to placebo. In addition, lenvantinib was proven to be non-inferior to sorafenib in term of OS in the REFLECT trial [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 24 studies included, one was a phase III randomized controlled trial (RCT) [ 8 ], and the other 23 were retrospective studies [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], involving 2438 patients with unresectable HCC who received first-line treatment with lenvatinib. The initial dose of oral lenvatinib was 12 mg QD for patients with a body weight of ≥60 kg, or 8 mg QD for those with a body weight of <60 kg.…”
Section: Resultsmentioning
confidence: 99%
“…The initial dose of oral lenvatinib was 12 mg QD for patients with a body weight of ≥60 kg, or 8 mg QD for those with a body weight of <60 kg. Of the 23 studies that assessed the tumor response, nineteen studies [ 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 22 , 23 , 24 , 25 , 27 , 28 , 31 , 32 , 33 , 34 , 35 ] applied the mRECIST, one [ 32 ] applied the RECIST 1.1, one [ 21 ] applied the RECIST 1.1 and mRECIST, and two [ 26 , 30 ] were unknown. Details of all studies and the characteristics of the patients are presented in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Недавно были опубликованы результаты сравнительных исследований ленватиниба с сорафенибом в реальной клинической практике [31,32].…”
Section: Discussionunclassified